Brain-inhabiting bacteria and neurodegenerative diseases: the “brain microbiome” theory - Arabi, Tarek Ziad; Alabdulqader, Aliyah Abdulmohsen; Sabbah, Belal Nedal; Ouban, Abderrahman (Frontiers in Aging Neuroscience, 2023)
Controversies surrounding the validity of the toxic proteinopathy theory of Alzheimer's disease have led the scientific community to seek alternative theories in the pathogenesis of neurodegenerative disorders (ND). Recent studies have provided evidence of a microbiome in the central nervous system. Some have hypothesized that brain-inhabiting organisms induce chronic neuroinflammation, leading to the development of a spectrum of NDs. Bacteria such as Chlamydia pneumoniae, Helicobacter pylori, and Cutibacterium acnes have been found to inhabit the brains of ND patients. Furthermore, several fungi, including Candida and Malassezia species, have been identified in the central nervous system of these patients. However, there remains several limitations to the brain microbiome hypothesis. Varying results across the literature, concerns regarding sample contamination, and the presence of exogenous deoxyribonucleic acids have led to doubts about the hypothesis. These results provide valuable insight into the pathogenesis of NDs. Herein, we provide a review of the evidence for and against the brain microbiome theory and describe the difficulties facing the hypothesis. Additionally, we define possible mechanisms of bacterial invasion of the brain and organism-related neurodegeneration in NDs and the potential therapeutic premises of this theory.